The Literacy City in Mataram: Linguistic Landscape Study - SETIAWAN, IRMA (PAROLE: Journal of Linguistics and Education, 2023)
The purpose of this study is to investigate and reconstruct spatial language patterns in Mataram as a Literacy City. The problem focuses on how are the forms and patterns of spatial language in Mataram as the embodiment of the Literacy City in NTB? Theory The research uses Linguistic Landscape Theory which describes lingual existence, linguistic ideology, and lingual competition. The research method uses a phenomenological approach with a qualitative descriptive type of research, although some information uses numerical data. The research target is in the form of spatial language in Mataram City with the most popular lingual pattern instruments, namely Indonesian, Jejawan script/Sanskrit, and Malay Arabic language/script. The research target can produce the formulation of spatial language patterns in Mataram City as the center of culture, economy, tourism, and government in NTB. The results of the study can model the spatial language scheme in Mataram city in two functions, the function of phrase-patterned and structured informationand linguistic interaction itself. The research findings are in the form of formulations or concepts from the literacy city model in Mataram with patterns that refer to spatial entities, populations, communities, and the distribution of texts with multi-character that are accessible to visitors.